International Handbook of Juvenile Justice
XXIV, 549 p.
Keywords: This comprehensive reference work presents an in-depth analysis on the juvenile justice systems of 19 different countries, both in EU-member states (old and new) and in the United States and Canada. The book is the result of research conducted by a group of outstanding scholars working in the field of juvenile justice. The book reflects a collective concern about trends in juvenile justice over the past two decades; trends that have begun to blur the difference between criminal and juvenile justice. The introduction highlights similarities and differences between the various systems, identifying three clusters of countries with a similar approach to juvenile justice. In particular, differences are found between the Anglo-Saxon countries, and continental Europe. The former have a more formal "justice" approach, with a strong emphasis on the accountability of juveniles, "just desert" principles, and retribution, while the latter still operate on a "welfare" philosophy. Two special systems, the Scottish Hearing system and the Scandinavian model, are presented as well.